Extraction of Pectin from Cantaloupe Peel Waste and Its Utilization in the Edible Coating for the Ripeness Quality Control of Mango cv. Nam Dok Mai Si Thong during Storage - Jakkranuhwat, Nattakan; Seedajhit, Orasa; Taksinakorn, Angkana; Whangsirikumchok, Supakorn (RMUTP Research Journal Sciences and Technology, 2025)
This study aimed to pectin was extracted from the cantaloupe peel wastes and then utilize it in the development of an edible coating to enhance the postharvest quality of mango cv. Nam Dok Mai Si Thong ripeness. First, the experimental design was 3 x 3 Factorial in CRD to study the optimization of pectin extraction conditions with 2 factors: citric acid at varying pH levels (1, 2 and 3) and the ratio of cantaloupe peel to citric acid (1:10, 1:30 and 1:50 by weight). The results indicated that the 1:50 (by weight) ratio of cantaloupe peel powder and citric acid extraction at pH 1 yielded the highest pectin (33.58±0.34%), accompanied by the lowest methoxyl pectin (%DE less than 50%). The purity of the extracted pectin met the standard required for commercial pectin manufacture. Then, the cantaloupe peel pectin, optimized for maximum yield, was utilized with 3 levels of pectin concentrations (10, 15, and 20% w/w), supplemented with 1% w/w glycerol and 0.04 g. of calcium chloride, was further utilized in an edible coating for mango cv. Nam Dok Mai Si Thong ripening quality preservation during storage at 13±2 °C for 18 days. The results showed that mangoes coated with 10 %w/w pectin exhibited the lowest weight loss and total soluble solids, as well as the greatest firmness compared to other conditions. This study highlights the added value of cantaloupe peel waste and offers a sustainable solution for enhancing the postharvest quality of mangoes.